Physical Basis of Multi-Energy Coupling-Driven Water Oxidation - Han, Zijiao; Yuan, Shun; Liu, Duanduan; Zheng, Qian; Huang, Yu An; Yan, Shicheng; Zou, Zhigang (Frontiers in Chemistry, 2022)
The hydrogen production by electrolyzing water is an important technique to store energy from renewables into chemical energy. Many efforts have been made to improve the energy conversion efficiency. In this Review article, we mainly summarized the emerging ideas on water oxidation by multi-energy coupling. The physicochemical nature of electrolyzing water reaction is firstly described. Then, we conceptually proposed the physical basis of energy coupling with a goal to maximize the energy conversion efficiency and showed the methods to achieve heat-electricity and magnetism-electricity coupling to drive water splitting. Finally, the materials requirement for creating efficient energy coupling water splitting system was proposed. These new ideas unlock a big potential direction for developing multi-energy coupling hydrogen production devices to efficiently store the intermittent and fluctuating renewables.